Pterostilbene Inhibits Lipogenic Activity similar to Resveratrol or Caffeine but Differently Modulates Lipolysis in Adipocytes. (19th June 2017) - Gomez‐Zorita, Saioa; Belles, Chloé; Briot, Anaïs; Fernández‐Quintela, Alfredo; Portillo, Maria P.; Carpéné, Christian
Abstract : The anti‐obesity effects of resveratrol shown in rodents are not transposed into an efficient therapy of human obesity. Consequently, the search for molecules mimicking or surpassing resveratrol actions is ongoing. The natural phenolic compound pterostilbene exhibits beneficial health effects and has the capacity to limit fat mass in animal models. In this study, we tested whether pterostilbene modulates triacylglycerol accumulation/breakdown. Prolonged exposure to pterostilbene or resveratrol inhibited adipocyte differentiation in 3T3‐F442A preadipocytes. Acute effects on lipolysis, antilipolysis and lipogenesis were determined for pterostilbene in mouse adipocytes, and compared with resveratrol. Pterostilbene was also tested on glycerol release and glucose uptake in subcutaneous human adipocytes. Dose–response analyses did not reveal a clear lipolytic effect in both species. The antilipolytic effect of insulin was improved by pterostilbene at 1–10 μM in mouse fat cells only, while at 1 mM, the phenolic compound was antilipolytic in human fat cells in a manner not additive to insulin. Pterostilbene dose‐dependently inhibited glucose incorporation into lipids similarly to resveratrol and caffeine. However, only the former did not inhibit insulin‐stimulated glucose uptake. Indeed, pterostilbene abolished the insulin lipogenic effect without inhibiting its antilipolytic action and rapid activation of glucose uptake. Pterostilbene therefore exhibits a unique panel of direct interactions with adipocytes that relies on its reported anti‐obesity and antidiabetic properties. Copyright © 2017 John Wiley & Sons, Ltd.